Zīj-i Yamīnī - al-Ḥaqāʾiqī, Muḥammad, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Islamic science, a zīj is an astronomical handbook made up of tables and text. Between the 2nd/8th and 13th/19th centuries, over 200 such works were written, many of them lost. Famous zīj are al-Zīj al-Ṣābiʾ by al-Battānī (ca 300/900), al-Qānūn al-Masʿūdī by al-Bīrūnī (421/1030), and Naṣīr al-Dīn al-Ṭūsī's (d. 672/1274) Zīj-i Īlkhānī . The Zīj-i Yamīnī published in facsimile here was compiled in Ghazna in 511/1156 by a certain Muḥammad al-Ḥaqāʾiqī and dedicated to the Ghaznavid ruler Bahrāmshāh b. Masʿūd b. Maḥmūd (reg. 511-552/1117-1157). It is the third oldest zīj in Persian, after the Zīj-i mufrad of Muḥammad b. Ayyūb Ṭabarī (485/1092) and the Persian translation of Kūshyār b. Labbān Gīlānī's (fl. ca. 390/1000) Arabic al-Zīj al-jāmiʿ by Muḥammad b. ʿUmar Munajjim-i Tabrīzī in 483/1090. Al-Ḥaqāʾiqī based himself on the works of others, notably al-Battānī's al-Zīj al-Ṣābiʿ , whose data he then recalculated for the city of Ghazna where necessary. Good example of early scientific Persian.